ANALISIS PENGARUH RASIO LIKUIDITAS, EFISIENSI, STRUKTUR MODAL, DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2005-2010 - , Randy Tulus Pangihutan Silalahi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Financial ratios can be trusted to provide a good indicator for the analysis. Financial ratio analysis based on historical financial data has a goal to give an indication of the company's performance in the future. Studies relating to the financial ratios have been carried out both by professionals and academics. By using information derived from financial ratios, investors can make predication of stock price movements. The purpose of this study was to identify the effect of liquidity ratios, efficiency, capital structure, and profitability on stock prices. Researchers used the method of hypothesis testing with multiple linear regression analysis model, and test the classical assumption. The data in this study were collected from the Indonesia Stock Exchange (www.idx.c.id). The results showed that the ratio of liquidity, capital structure, and profitability (OPM) have a significant effect on stock prices, the ratio of efficiency and profitability (ROA) had no significant effect on stock prices. Simultaneously liquidity ratios, capital structure, profitability, and efficiency have a significant effect on stock prices.